EFFECT OF WORK LIFE BALANCE AND COMPENSATION ON JOB SATISFACTION AT KOPERASI SETIA BHAKTI WANITA SURABAYA - fatmawati, selly; Irbayuni, Sulastri (Jurnal Ekonomi Balance, 2021)
Human resources are an important resource in a company because human resources determine the success of an organization, both institutions, and companies. Therefore, companies need to pay attention to work-life balance and employee compensation properly so that employee job satisfaction in the company continues to increase. This study aims to determine the effect of work-life balance and compensation on employee job satisfaction at the Women's Cooperative Setia Bhakti Wanita Surabaya. The research method used is a quantitative method and data collection using a questionnaire using a five-point Likert scale as a measuring tool. The population and samples used in this study were all permanent employees at the Setia Bhakti Wanita Surabaya Cooperative with a total of 40 employees. The data used are primary data and secondary data while the analysis used is Partial Least Square (PLS). Based on the results of research that has been done: 1). Work-Life Balance that can be managed properly can also have a good influence on employee job satisfaction at the Setia Bhakti Wanita Cooperative of Women Surabaya 2). Good compensation has a good influence on employee job satisfaction at the Setia Bhakti Wanita Surabaya Cooperative.